Dual Commitment to the Organization and the Union: A Multi-Dimensional Approach - Cohen, Aaron (Relations industrielles / Industrial Relations, 2005)
This study examines the multi-dimensional nature of the dual commitment to the organization and the union. Most research that has examined this concept has used only one dimension for each commitment. The most established, multi-dimensional scales of organizational and union commitment were examined in their relationship to work and union correlates. The participants were 489 members (a 65% response rate) of the Union of Nurses in Israel. The findings showed that while affective commitment and union loyalty are related to the correlates examined here, the additional dimensions added significant variance to the results already explained by affective commitment and union loyalty. For example, normative commitment is related to four correlates and the variable “willingness to work for the union” is also strongly related to the correlates. The study concluded that utilizing only one dimension to examine each commitment might result in the loss of valuable information on dual commitment.